2019
DOI: 10.51894/001c.7961
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic Evaluation of the Quadriceps Tendon in Cadaveric Specimens: Application for Anterior Cruciate Ligament Reconstruction Graft Choice

Abstract: The quadriceps tendon (QT) is an autograft option for primary and revision anterior cruciate ligament (ACL) reconstruction. Techniques for predicting the appropriate graft size are limited. The purpose of this study was to evaluate the morphologic features of the QT in cadaveric specimens and compare the findings to recent MRI studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 26 publications
0
7
1
Order By: Relevance
“…It is important to note that the height of a subject and the length of limb in the same subject may not be directly related. Interestingly, none of the parameters paired with the LLL showed a strong correlation unlike in previous reports byXerogeanes et al (2013) andKrebs et al (2019) that found a strong correlation between the height of individual and the tendon length.…”
contrasting
confidence: 91%
See 2 more Smart Citations
“…It is important to note that the height of a subject and the length of limb in the same subject may not be directly related. Interestingly, none of the parameters paired with the LLL showed a strong correlation unlike in previous reports byXerogeanes et al (2013) andKrebs et al (2019) that found a strong correlation between the height of individual and the tendon length.…”
contrasting
confidence: 91%
“…Unfortunately, there is no report in the literature to compare with the present findings, so it is not discussed further. The data on the surface area of the QT may be of benefit to the rate of recovery at the harvest site, since the QT has been shown to have more collagen content (Hadjicostas et al, 2007) which contributes to its tensile strength (Shani et al, 2016;Krebs et al, 2019;Latiff and Olateju, 2022). The implication of this is that the remaining collagen content after the harvesting of a graft should be sufficient for the QT to recover quicker and function more satisfactorily than the patellar tendon, which has a lesser collagen content (Hadjicostas et al, 2007) and a smaller surface area than the QT (unpublished report).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tendon strength is attributed to collagen content and the QT has an advantage over the PT because it has a more (approximately 20%) collagen content [20] which enables the QT to endure a higher load to failure and strength than the PT [21,22]. Considering the surface areas of the QT and the PT, the implication of this is that the remaining collagen content after the harvesting of a graft should be sufficient for the QT to function more satisfactorily than the PT with a lesser collagen content due to its surface area.…”
Section: Discussionmentioning
confidence: 99%
“…Specimen number was chosen based on previous studies. 5 , 12 , 17 , 25 The cadaveric specimens used in this study were donated to a tissue bank for the purpose of medical research and then purchased by our institution. Specimens were excluded if there was any evidence of previous knee surgery or the presence of osteophytes on the proximal aspect of the patella.…”
Section: Methodsmentioning
confidence: 99%